Regulating Transitions from School to Work An Institutional Ethnography of Activation Work in Action - Dahmen, Stephan (2021)
How are activation programs for the young unemployed implemented? How do street-level bureaucrats deal with competing rationalities and demands for action? Transition policies increasingly aim at promoting self-regulation and constructing employable subjects. Stephan Dahmen explores the practical regulation of biographical transitions in activation programs for the young unemployed by focusing on the interactive accomplishment of activation work. The study reveals how the critical tensions of activation policies are continually re-interpreted and adapted to local contingencies and describes the various organisational technologies used for creating employable subjects.